The Structure of Linkers Affects the DNA Binding Properties of Tethered Dinuclear Ruthenium(II) Metallo‐Intercalators. Issue 23 (20th February 2017) - Saeed, Hiwa K.; Saeed, Ibrahim Q.; Buurma, Niklaas J.; Thomas, Jim A.
Abstract: With the long‐term aim of enhancing the binding properties of dinuclear Ru II ‐based DNA light‐switch complexes, a series of eight structurally related mono‐ and dinuclear systems are reported in which the linker of the bridging ligand has been modulated. These tethered systems have been designed to explore issues of steric demand at the binding site and the thermodynamic cost of entropy loss upon binding. Detailed spectroscopic and isothermal titration calorimetry (ITC) studies on the new complexes reveal that one of the linkers produces a dinuclear system that binds to duplex DNA with an affinity ( K b >10 7  m −1 ) that is higher than its corresponding monometallic complex and is the highest affinity for a non‐threading bis‐intercalating metal complex. These studies confirm that the tether has a major effect on the binding properties of dinuclear complexes containing intercalating units and establishes key design rules for the construction of dinuclear complexes with enhanced DNA binding characteristics. Abstract : Strengthening links : The DNA binding properties of non‐threading dinuclear Ru II (dppz) bis‐intercalators are highly dependent on the nature of their linker ligand. Judicious selection of the connectivity and structure of the tether enhances binding by two orders of magnitude compared to previously reported systems.